Otimização e planejamento da alocação de capital em instituições financeiras considerando os requisitos do acordo de Basiléia II para o risco de crédito - Barros Filho, Cicero Venancio (2010)
The regulation has influenced the attitudes of financial institutions when related to Risk assumption. The global financial market admits the necessity to quantify and control risks inherent to banking activities, processes which are converging to a standard in almost all countries. Following recommendations of Basel Committee on Banking Supervision (BCBS), regulatory agencies apply, in many countries, rules to size the minimum capital requirement in financial institutions. Aiming to offer a link of ideas, the first chapter will reference concepts, definitions and approaches about risk in financial institutions, related to the evolution of perception, theories for analysis and considerations about the interrelationship between these risks. The creation of central banks linked to historical framework of global financial crisis is addressed in the second chapter, focusing the creation process of bank regulation. In the third chapter are presented, as the main object of this study, parameters projections relating to capital allocation, in order to attend new managerial requirements in financial institutions, considering the optimization of returns on the risk-weighted assets and strategic planning for expansion capital and credit lines, in accordance with the requirements standardized by the banking supervisory agencies. The final considerations demonstrate the applicability of these projections as support for risk management policies and capital allocation in financial institutions.